Diversity of Wildlife in the Campus of Bangladesh Forest Research Institute: an Area for Successful Wildlife Conservation in a City of Bangladesh - Rahman, M. M.; Rahman, M. A.; Islam, M. K.; Mainuddin, S. M. (International Journal of Bio-resource and Stress Management, 2023)
Genetic variability and heritability of different characters were studied using 32 genotypes including two standard checks in green gram (Vigna radiata L.). The genotypes showed wide range of variation for all the characters. A high coefficient of variation was observed for seed yield plot-1 and number of pods plant-1. High values of heritability coupled with high genetic advance as percentage of mean was observed for seed yield plot-1 and this character can be improved by selection. The days to maturity, number of clusters plant-1 was significantly and positively correlated with yield. Number of clusters plant-1 exerted maximum direct effect on seed yield followed by number of pods cluster-1, pod length and number of seeds pod-1 had positive direct effect on seed yield.